Determination of pediatric nurses’ knowledge of and attitudes towards childhood autism and CT recommendations - Çiğdem Erdoğan; Türkan Turan (Trends in Pediatrics)
Objective: The study aimed to determine the knowledge levels and attitudes of nurses working in pediatric clinics on childhood autism and which complementary therapies (CT) methods they recommend to support children with autism.